A theoretical framework on Organizational Justice and Workplace Deviance - Dosanjh, Priyanka; Rao , S.Srinivas (International Journal of Psychosocial Rehabilitation, 2020)
The study of justice perceptions is an important area of research in organizational behavior studies because of its relationship to relevant individual and organizational outcomes (Cohen-Charash and Spector, 2001). Employees develop different types of justice assessments related to outcomes, decisions or interactions patterns within organization. Injustice or unfair treatment with employees leads to various types of deviant behavior at workplace as desired like stress, absenteeism, non-performance, politics, retaliatory intentions and turnover tend to increase (Colquitt et. al, 2001; Nirmala & Akhilesh, 2006). It may also lead to lower commitment levels, psychological disownership, psychological contract withdrawal etc due to dissatisfaction and demotivation arise because of unfair treatment (Pizzino, 2002). Workplace deviant behaviour is a prevailing and costly phenomenon that includes a wide range of negative acts conducted by employees to harm the organization and its members either voluntarily or involuntary. Research indicates that organizational justice is a dominant predictor of workplace deviant behaviour (Fatt, 2010). Specifically, the justice perspective proposes that workplace deviance is a reaction to the unfairness perceived by employees at their workplace. A rich body of research has investigated the relationship between employee’s fairness perceptions and various forms of workplace deviant behaviours. Yet, to date, a comprehensive review of the literature is unavailable that summarizes and integrates this stream of research. This study makes an attempt to understand the antecedents and to explain the relationship of organizational justice on workplace deviance behaviour to present at comprehensive framework to offer empirical studies in future research.